STUDY ON EFFECT OF AZOXYSTROBIN ON SHELF LIFE OF FRESH CUSTARD APPLE FRUITS ARD APPLE FRUITS - NETRAVATI,; SURESH, G. J.; JAGADEESH, L. (The Bioscan, 2018)
An attempt was made to study the efficacy of postharvest treatment of azoxystrobin on the keeping quality of fresh custard apple fruits under cold storage. The custard apple fruits were treated with different concentrations of azoxystrobin and the results revealed that the fruits treated with 0.2 per cent azoxystrobin for 5 minutes had minimum per cent weight loss (5.42±0.30), least respiration rate (24.85 mlCO2/kg/hr), maximum firmness (3.36N), maintained good color values of peel viz., L* 51.32; b* 28.41; C* 31.54; and ho 90.70 and minimum a* value (-1.16). The treatments also maintained good pulp color values viz., L* 46.13; b* 11.86; C* 9.95; and ho 92.10, and minimum a* value (-0.96) and higher sensory scores with respect to appearance (4.75), texture (4.88) and taste and flavour (4.88) at the end of 12 days of cold storage as compared to other treatments. These results show that azoxystrobin is a potential candidate and has immense scope to be used as a post harvest treatment to increase the shelf life of the fruits.